Antioxidative Action of Ellagic Acid-A Kinetic DFT Study - Jelena Tošović; Urban Bren (MDPI AG, 2020)
Although one can find numerous studies devoted to the investigation of antioxidative activity of ellagic acid (EA) in the scientific literature, the mechanisms of its action have not yet been fully clarified. Therefore, further kinetic studies are needed to understand its antioxidative capacity completely. This work aims to reveal the underlying molecular mechanisms responsible for the antioxidative action of EA. For this purpose, its reactions with HO• and CCl3OO• radicals were simulated at physiological conditions using the quantum mechanics-based test for overall free-radical scavenging activity. The density functional theory in combination with the conductor-like polarizable continuum solvation model was utilized. With HO• radical EA conforms to the hydrogen atom transfer and radical adduct formation mechanisms, whereas sequential proton loss electron transfer mechanism is responsible for scavenging of CCl3OO• radical. In addition, compared to trolox, EA was found more reactive toward HO•, but less reactive toward CCl3OO•. The calculated rate constants for the reactions of EA with both free radicals are in a very good agreement with the corresponding experimental values.